Successful Coaching - Martens, Rainer, 1942- (Champaign, Ill. ; Leeds : Human Kinetics, 2004)
This comprehensive text includes content on how to communicate and motivate players, as well as manage problem behaviours among athletes with a positive approach. It provides a full introduction to the games approach to coaching and strategic advice on how to incorporate this into a successful programme.
Previous ed.: 1997.
Includes index.
Keywords: Coaching (Athletics); Sport